Preparation and Degradation Behavior of Polycaprolactone Nanoporous Membrane - Naini Guo (Science Faculty of Chiang Mai University, 2019)
Polycaprolactone (PCL) was semi-crystalline linear aliphatic polyester and prepared by e-caprolactone ring opening polymerization, which was a kind of completely degradable environmentally friendly polymer materials. In this work, PCL nanoporous film was prepared by the thermal induced phase separation (TIPS). The initial decomposition temperature was 295 °C and the maximum weight loss rate temperature was 402 °C that were analyzed by the thermo gravimetric analyzer (TG). The original homogeneous nanohole about 200 ~ 400 nm and degradation of unstructured surface were observed by scanning electron microscopy (SEM). The fracture of ester bonds in the degradation of different solutions was confirmed by the infrared spectrum (FI-IR), under acidic or alkaline conditions, the fracture of the ester bond is accelerated by electrolyte ionization in the solution. However, there is no ionization at neutral conditions leading to slower fracture rate of ester bonds. The optimum degradation property of PCL nanoporous membrane was in 0.5 mol/L alkaline solution, and the mass loss rate could reach 100% after 60 days of degradation.